2022
DOI: 10.1111/omi.12366
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐34 permits Porphyromonas gingivalis survival and NF‐κB p65 inhibition in macrophages

Abstract: Interleukin‐34 (IL‐34) is a cytokine that supports the viability and differentiation of macrophages. An important cytokine for the development of epidermal immunity, IL‐34, is present and plays a role in the immunity of the oral environment. IL‐34 has been linked to inflammatory periodontal diseases, which involve innate phagocytes, including macrophages. Whether IL‐34 can alter the ability of macrophages to effectively interact with oral microbes is currently unclear. Using macrophages derived from human bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 108 publications
(163 reference statements)
0
5
0
Order By: Relevance
“…When P. gingivalis attacks, innate immune cells, including neutrophils and macrophages, are recruited to the local tissue as the first line of the host immune defense system and eliminate the invading pathogens through phagocytosis and further varieties of pathogen‐killing mechanisms (Almarghlani et al, 2022; Cekici et al, 2014). The clearance of invading P. gingivalis by neutrophils involves a series of functions, such as neutrophils adhesion and chemotaxis, phagocytosis of pathogens, and pathogen killing mechanisms, including nicotinamide adenine dinucleotide phosphate (NADPH, NOX)‐dependent respiratory burst function, and the formation of NETs (Chen, Tong, et al, 2022; Gu et al, 2020; Liu et al, 2021; Mikolai et al, 2020; Raad et al, 2019).…”
Section: The Role Of Zinc In Periodontal Inflammationmentioning
confidence: 99%
“…When P. gingivalis attacks, innate immune cells, including neutrophils and macrophages, are recruited to the local tissue as the first line of the host immune defense system and eliminate the invading pathogens through phagocytosis and further varieties of pathogen‐killing mechanisms (Almarghlani et al, 2022; Cekici et al, 2014). The clearance of invading P. gingivalis by neutrophils involves a series of functions, such as neutrophils adhesion and chemotaxis, phagocytosis of pathogens, and pathogen killing mechanisms, including nicotinamide adenine dinucleotide phosphate (NADPH, NOX)‐dependent respiratory burst function, and the formation of NETs (Chen, Tong, et al, 2022; Gu et al, 2020; Liu et al, 2021; Mikolai et al, 2020; Raad et al, 2019).…”
Section: The Role Of Zinc In Periodontal Inflammationmentioning
confidence: 99%
“…IL-8 is continuously expressed in periodontal tissues and mediates the recruitment of neutrophils to gingival tissues 26 . Studies have reported that IL-8 expression is significantly increased in periodontal disease and is associated with the occurrence of periodontitis 27 , 28 . Moritz et al demonstrated that as the severity of periodontal lesions increases, neutrophil recruitment mediated by CXCL6 can supplement the recruitment pathway of IL-8 21 .…”
Section: Discussionmentioning
confidence: 99%
“…The other primary fimbriae, known as FimA, is a TLR2 agonist targets thereby inhibit the autophagic degradation of P. gingivalis, which may also facilitate its dissemination to distant sites within DCs (El-Awady et al, 2015). Furthermore, another investigation revealed that macrophages subjected to differentiation in the presence of IL-34, a predominant cytokine in the oral gingival environment, exhibit significantly diminished capacity to eliminate engulfed P. gingivalis (Almarghlani et al, 2022). In conclusion, P. gingivalis exhibits a remarkable capacity to evade immune defenses and establish persistence within diverse cell types, notably DCs and macrophages.…”
Section: Oral Pathogens In the Carcinogenesis Of Colon Cancermentioning
confidence: 93%